Mediator Architecture and RNA Polymerase II Interaction. Issue 12 (19th June 2016) - Plaschka, Clemens; Nozawa, Kayo; Cramer, Patrick
Abstract: Integrated structural biology recently elucidated the architecture of Mediator and its position on RNA polymerase II. Here we summarize these achievements and list open questions on Mediator structure and mechanism.